Rozkłady zwinięte względem ustalonego punktu - Miszczak, Witold (Distributions rolled up towards the fixed point, 2005)
In the paper is presented a distribution of any random variable X with a density function given by: , , Jf(x) + f(2y-x) forx~L y, [0 for x < y, where f(jc) is a basic density function. This density function characterizes a distribution that we have named as the „rolled up” the point y. Examples of such distributions are given for uniform and normal distributions. For g(jt) such parameters are calculated as expected value and variance.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1097, s. 88-94